2012
DOI: 10.1159/000342643
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urinary Tract Symptoms in Benign Prostatic Hyperplasia Patients: Orchestrated by Chronic Prostatic Inflammation and Prostatic Calculi?

Abstract: Objective: This study aims to examine the relationship between chronic prostatic inflammation and prostatic calculi, and clinical parameters of benign prostatic hyperplasia (BPH). Materials and Methods: This study was based on 225 patients who underwent transurethral resection of the prostate for BPH. Chronic inflammation was graded as 0 (n = 44), I (n = 54), II (n = 88) or III (n = 39) according to severity. Prostatic calculi were classified into types A (n = 66), B (n = 44), M (n = 77) and N (n = 38). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 51 publications
1
26
1
9
Order By: Relevance
“…Previous studies have reported that there may be a relationship between an increase in prostate volume and the incidence of PCal [19,20]. In our study, the PCal+ group had a higher prostate volume than the PCal-group, but this difference was not significant (51.63 vs .50.85, p = 0.7).…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies have reported that there may be a relationship between an increase in prostate volume and the incidence of PCal [19,20]. In our study, the PCal+ group had a higher prostate volume than the PCal-group, but this difference was not significant (51.63 vs .50.85, p = 0.7).…”
Section: Discussioncontrasting
confidence: 75%
“…However, there is increasing evidence linking histologic prostate inflammation with benign prostate hyperplasia (BPH) and degree of lower urinary tract symptoms (28,29). For example, a previous study using data from the REDUCE trial found significant correlation between chronic inflammation and urinary symptoms (17).…”
Section: Discussionmentioning
confidence: 99%
“…Most calculi associate with inflammatory changes in prostate acini including lymphocyte and histiocyte infiltration. [14][15][16][17][18] Calcifications induced by inflammation generate a microenvironment to drive more inflammatory change. Prostatic calcification obstructs the intraprostatic ducts, which leads to an inflammatory response in prostatic tissue characterized by lymphocyte infiltration, cytokine activation, and release of reactive oxygen species.…”
Section: Commentmentioning
confidence: 99%